Kajian Ekonomi Dan Marjin Pemasaran Usahatani Kacang Panjang (Vigna sinensis L.) di Kelurahan Bagan Pete Kecamatan Alam Barajo Kota Jambi - Wiwin Alawiyah; Rogayah Rogayah (Jurnal MeA (Media Agribisnis), 2022)
One of the goals of farmers as producers in their business is to obtain high yield. To achieve high production, producers face several constraints as a determining factor in making decisions because the high production must be balanced by providing comparable inputs and inputs in the form of capital. This capital  must be returned by marketing the output obtained. The production activities carried out will be better if   economically   can cover the costs sacrificed in the production process. This research was conducted in Jambi City. Long bean farming was in Bagan Pete Village, Alam Barajo District, Jambi City and was one of the centre for vegetable farming. Long bean plants began to produce yields after the plants were 45 days old. The average land area cultivated by the farmers was 168.29 m2. The average income was Rp.5.840.585/periode.  The average use of labor in the family with working time ranged   7-8 hours / day. The marketing margin was IDR 7,000/kg.